Towards sustainable lake restoration - Tammeorg, Olga; Kragh, Theis; Nürnberg, Gertrud K.; Carvalho, Laurence; Huser, Brian; Jilbert, Tom; Augustyniak-Tunowska, Renata; Dadi, Tallent; Friese, Kurt; Grinberga, Laura; Grochowska, Jolanta K.; Haande, Sigrid; et al. (Elsevier BV, 2026)
Sustainable lake restoration has been introduced recently as a strategy to address ecological, economic, and social challenges in nutrient management. The strategy would benefit at least 40 % of the world's lakes through addressing eutrophication, and the impact becomes even broader if we consider the complex nature of eutrophication (its linkage to multiple environmental problems). This approach involves: 1) demonstrating broader social and economic benefits, 2) integrating circular economies, and 3) directly engaging local communities in co-developing restoration goals, targets and monitoring. The current study explores opportunities to advance sustainable lake restoration using a well-established model that fosters interaction among restoration stakeholders. We assessed each model step for sustainability needs, identifying knowledge gaps and key factors for future success. We emphasize the need for a better understanding of the linkages between eutrophication and other environmental problems, proper monitoring programs to demonstrate broader restoration benefits, effective system analysis tools, sustainable nutrient recycling measures and accurate realization, and thorough documentation for life-cycle assessments. Achieving these goals requires significant policy and financing transformations, continuous engagement, and close collaboration among all stakeholders.